Breeding approach and progress made in the SADC/CIAT Bean Program in Malawi - Aggarwal, VD; Mbvundula, AD (International Center for Tropical Agriculture, 1992)
The SADC/CIAT bean program to serve the more southern latitudes started in 1991 in Malawi with the arrival of a bean breeder. A large number of germplasm lines introduced from CIAT, Colombia and from the national programs in the region were evaluated at Bunda and Dedza for disease resistance, general adaptation and yield. A wide variation in yield and resistance to diseases was observed. Promising lines have been selected for inclusion in a zonal nursery to be sent to participating national programs in the 1992-93 crop season. A program to screen germplasm for tolerance to Al toxicity was initiated at the Lunyangwa research station in Malawi. Aluminium toxicity was modified in field trials by adjusting soil pH with lime. A contrasting response to varying levels of acidity was observed. Crosses have been initiated to improve the locally adapted varieties for resistance to diseases, high yield and tolerance to Al toxicity. Several regional activities were undertaken that included a zonal yield trial distributed to seven countries, a breeders` travelling workshop, and visits to several countries in the region to interact with other national programs